Integrasi Pembelajaran Mendalam dengan Metode Mindful, Meaningful, dan Joyful untuk Optimalisasi Hasil Pendidikan - Huda, Choerul; Fahmi Hidayutullah, Muhammad (Al Fattah Ejournal Sma Al Muhammad Cepu, 2025)
Effective education focuses not only on academic outcomes, but also on students' emotional and social development. This study aims to explore the influence of integrating deep learning withmindful, meaningful, and joyful methods in improving educational outcomes. This type of research is qualitative with a case study approach. The data sources consist of teachers, students, and principals in several schools that have implemented the three methods. Data collection techniques were conducted through in-depth interviews, classroom observations, and documentation. The purpose of this study was to analyse how the integration of the three methods can affect students' academic outcomes, emotional well-being, and social interactions. The results show that the application of mindful methods helps students to focus more and reduce anxiety, while meaningful learning increases the relevance of teaching materials to students' lives, which deepens their understanding. The joyful method creates a fun learning atmosphere and increases students' intrinsic motivation. Overall, the integration of these three methods has a positive impact on educational outcomes, both in the cognitive, emotional and social aspects of students, as well as creating a more holistic and meaningful learning experience.